PRESENCIA DE HUANCAS EN UN SECTOR DE LA CUENCA SUPERIOR DEL RIO HUATATA, CHIARA—AYACUCHO - Carhuas Tenorio, Héctor (2017)
This paper is a report from a superficial recognition, in a sector of the dust Huatata River basin. Includes the territories of the current Community campesina San Martin of Yanapiruro and Ichubamba, district of Chiara, province of Huamanga (Ayacucho). During the record surface identified a high number of huancas of different forms and sizes, distributed in the top and slopes of several hills between 3900 to 4300 meters above sea level. From the archaeological record and detailed description we examined on the basis of the information ethnohistorical and works relating to the topic to achieve new data to the community in general.